Ovopel and Carp Pituitary Extract as Spawning Inducers in Males of the Amazon Catfish Leiarius marmoratus (Gill, 1970) - João Ênio Xavier Souza Araújo; Danilo Pedro Streit; Janessa Sampaio de Abreu Ribeiro; Edenilce de Fátima Ferreira Martíns; Francielle Novaes Souza; Carlos Antônio Lopes de Oliveira; Ricardo Pereira Ribeiro; Nelson Maurício Lopera-Barrero; Jayme Aparecido Povh (2014)
The objective of this study was to evaluate Ovopel and carp pituitary extract as spawning inducers in the males of the Amazon catfish L. marmoratus. The following treatments, applied in a single dose, were studied: 0.2, 0.4 and 0.6 Ovopel pellet/kg live weight, and 2.5 mg carp pituitary extract/kg live weight. Each treatment was repeated four times. No significant difference in sperm volume, motility and vigor, time of motility, sperm count, or percentage of normal and abnormal spermatozoa was observed between the treatments. There was also no significant difference in terms of primary or secondary sperm defects, except for the secondary defect of loose heads, which was less frequent in the treatments using 0.4 and 0.6 Ovopel pellet/kg live weight. It was concluded that Ovopel could replace carp pituitary extract for induction spawning in the males of the Amazon catfishL. marmoratus.